ZONING OF FLOOD PRONE AREAS IN SINGKAWANG CITY DUE TO RAINFALL - Razi, Fahrul; Soeryamassoeka, SB; Yulianto, Eko (Jurnal Teknik Sipil, 2023)
Singkawang City is a coastal and hilly city. Flooding incidents have caused considerable material damage, displacement of people, and loss of lives. Floods in Singkawang occur almost yearly. In general, the floods in Singkawang are caused by natural factors, exceptionally high rainfall. Considering the significant impact of floods on the development of Singkawang City, it is necessary to establish flood vulnerability zoning based on rainfall in the city.An analysis is conducted on parameters that influence flood incidents, including the slope of the land, elevation, soil type, land cover, and hydrological analysis of rainfall data to create a flood vulnerability zoning map in Singkawang City. Then, an overlay is performed on the four parameters that affect floods, resulting in a map showing the distribution of inundation due to the maximum planned flood discharge (Q) generated from the hydrological analysis based on rainfall.The flood vulnerability map analysis results based on 4 data parameters that affect flood events obtained that the flood-safe area in Singkawang City covers an area of 14863.97 ha (27.04%). In contrast, areas not prone to floods cover 24571.74 ha (44.70%). Areas vulnerable to floods cover 11476.22 ha (20.87%), and regions highly vulnerable to floods cover 3567.28 ha (6.49%). Based on the results of hydrological analysis based on rainfall, it is obtained that the area of Singkawang City mostly experiences inundation due to the maximum planned flood discharge occurring at a 2-year interval in the Small Semelagi River Zone (353.5 ha), at a 5-year gap in the Small Semelagi River Zone (327.4 hectares), at a 10-year gap in the Selakau River Zone (401.4 ha), at a 20-year interval in the Selakau River Zone (473.1 ha), at a 50-year interval in the Selakau River Zone (545.9 ha), and at a 100-year gap in the Selakau River Zone (617.7 ha).